Mechanochemical Synthesis of PdO2 Nanoparticles Immobilized over Silica Gel for Catalytic Suzuki–Miyaura Cross-Coupling Reactions Leading to the C-3 Modification of 1H-Indazole with Phenylboronic Acids - Qin Pan; Yong Wu; Aqun Zheng; Xiangdong Wang; Xiaoyong Li; Wanqin Wang; Min Gao; Zainab Bibi; Sidra Chaudhary; Yang Sun (Molecules, 2023)
The C-3 modification of 1H-indazole has produced active pharmaceuticals for the treatment of cancer and HIV. But, so far, this transformation has seemed less available, due to the lack of efficient C-C bond formation at the less reactive C-3 position. In this work, a series of silica gel-supported PdO2 nanoparticles of 25–66 nm size were prepared by ball milling silica gel with divalent palladium precursors, and then employed as catalysts for the Suzuki–Miyaura cross-coupling of 1H-indazole derivative with phenylboronic acid. All the synthesized catalysts showed much higher cross-coupling yields than their palladium precursors, and could also be reused three times without losing high activity and selectivity in a toluene/water/ethanol mixed solvent. Although the palladium precursors showed an order of activity of PdCl2(dppf, 1,1′-bis(diphenylphosphino)ferrocene) > PdCl2(dtbpf, 1,1′-bis(di-tert-butylphosphino)ferrocene) > Pd(OAc, acetate)2, the synthesized catalysts showed an order of C1 (from Pd(OAc)2) > C3 (from PdCl2(dtbpf)) > C2 (from PdCl2(dppf)), which conformed to the orders of BET (Brunauer–Emmett–Teller) surface areas and acidities of these catalysts. Notably, the most inexpensive Pd(OAc)2 can be used as a palladium precursor for the synthesis of the best catalyst through simple ball milling. This work provides a highly active and inexpensive series of catalysts for C-3 modification of 1H-indazole, which are significant for the large-scale production of 1H-indazole-based pharmaceuticals.